Pengaruh Motivasi dan Pemahaman Materi terhadap Minat Karier Mahasiswa Akuntansi menjadi Akuntan - Riski Meilinawati,; Anik Yuliati, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Career is a process of learning and opportunities in the life journey of individuals to improve their standard of living. The financial and corporate sector in Indonesia is experiencing rapid development. This is not in line with the number of accountants in Indonesia which is still not balanced with the number of accounting graduates. This study aims to determine the effect of motivation and understanding of the material on the career interest of students of the Accounting Study Program for a Career in the Accounting Field. This study used a purposive sampling method, and obtained a population of 293 students. The sample is calculated using the slovin formula and the results are 74 respondents. The data collection technique used a questionnaire and the answers were measured using a Likert scale. Data were analyzed using multiple linear regression tests. The results of this study indicate that motivation and material understanding have a significant effect on the interest of accounting students to become accountants.